The relationship between self-efficacy and error orientation of nursing students during clinical internships: a cross-sectional study - Guo, Yuanli; Fan, Wenfeng; Dong, Xiaofang; Yang, Caixia; Wang, Min; Gao, Huanhuan; Lv, Peihua; Ma, Keke (Frontiers in Public Health, 2024)
Background Nursing students often make clinical errors due to their limited clinical experience and their orientation toward errors, revealing their attitude and behavioral tendencies regarding nursing errors. Understanding how self-efficacy, motivation, and a sense of security influence the error orientation of nursing students is important for developing strategies to enhance their error orientation. Objectives This study aimed to explore the relationship between self-efficacy, motivation, and error orientation of nursing students during clinical internships. Method This was a cross-sectional study. An electronic questionnaire was distributed to nursing students from 14 September 2023 to 30 September at a comprehensive tertiary A teaching hospital in Zhengzhou, Henan province. The instruments used in this study included the General Information Questionnaire, General Self-efficacy Scale, Achievement Motives Scale, Security Scale, and Error Orientation Scale. Statistical Product and Service Software Automatically (SPSSAU) was used to perform statistical description, mediation analysis, and moderated mediation analyses. Results A total of 510 nursing students were included in this study. The motivation for success and failure-escaping fully mediated the relationships between self-efficacy and error orientation of nursing students, with a mediation effect of 0.101 (95% CI: 0.058–0.144). The security of nursing students moderated both the direct effect of this model and the indirect effect of motivation for failure-escaping. When security was high, the self-efficacy of nursing students was positively correlated with their error orientation, with an effect of 0.059 (95% CI: 0.003 0.116). When security was high, the moderation effect was significant, with an effect of −0.012 (95% CI: −0.026 -0.002). However, at low and median levels of security, the mediation effect was non-existent. Conclusion The motivation for success and failure escaping play different roles in the paths between self-efficacy and error orientation. Clinical nursing teachers should take measures to enhance the motivation for success but reduce the failure-escaping motivation to improve the error orientation of nursing students. Additionally, it is crucial to pay attention to and improve the sense of security of students during clinical internships.